Crime without borders : an introduction to international criminal justice - Fichtelberg, Aaron (Upper Saddle River, N.J. : Pearson/Prentice Hall, 2008)
"Globalization is a fundamental part of the modern world. As transportation and communications technology develops and makes cross-border communication and transportation easy, a whole new world has opened up to Americans. Using the internet, we can access information and entertainment instantly from every part of the world. We can buy products that are quickly and easily shipped from China, India, or Europe. And we can sell our goods to them, too." "This book is an introduction to some of these developments in international criminal justice. On one hand we will look at how different criminal justice institutions have developed to fight crimes that cross international boundaries, looking at the legal and law enforcement developments that make this possible. On the other hand, we will also examine institutions that are designed to try and punish offenders internationally, for offenses that they are immune to at home. Thus, we look at national cooperation on transnational crimes and international institutions that deal with particularly horrible crimes such as genocide and crimes against humanity. Finally, we examine the global crime problems themselves, looking at how these problems developed historically, how they currently function, and how different criminal justice institutions seek to fight them."--BOOK JACKET.
Includes bibliographical references (pages 288-302) and index.
Keywords: Criminal justice, Administration of -- International cooperation; Judicial assistance -- International cooperation; Criminal jurisdiction -- International cooperation